Double bank runs and liquidity risk management - Filippo Ippolito; José-Luis Peydró; Andrea Polo; Enrico Sette (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2016)
By providing liquidity to depositors and credit line borrowers, banks are exposed to doubleruns on assets and liabilities. For identification, we exploit the 2007 freeze of the European interbank market and the Italian Credit Register. After the shock, there are sizeable, aggregate double-runs. In the cross-section, pre-shock interbank exposure is (unconditionally) unrelated to post-shock credit line drawdowns. However, conditioning on firm observable and unobservable characteristics, higher pre-shock interbank exposure implies more post-shock drawdowns. We show that is the result of active pre-shock liquidity risk management by more exposed banks granting credit lines to firms that run less in a crisis.
Keywords: G01; G21; G28; 330; Credit lines; Liquidity risk; Financial crisis; Runs; Risk management